2021
DOI: 10.1073/pnas.2025813118
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory T helper 17 directly harms oligodendrocytes in neuroinflammation

Abstract: Significance Multiple sclerosis (MS) is a neuroinflammatory, demyelinating disease that represents one of the most frequent causes of irreversible disability in young adults. Treatment options to halt disability are limited. We discovered that T helper (Th)17 cells in contact with oligodendrocytes produce higher levels of glutamate and induce significantly greater oligodendrocyte damage than their Th2 counterpart. Blockade of CD29, which is linked to glutamate release pathways and expressed in high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…In addition, we established that Th17-polarized cells induce both OL process damage and OL cell death in mouse and human systems. While we identified the contribution of CD29-triggered glutamate secretion by Th17-polarized cells to OL process injury and myelination impairment, glutamate did not induce death of human OLs in primary culture ( 17 ). Human OLs are highly resistant to induction of programmed cell death upon exposure to stressors such as high doses of tumor necrosis factor alpha (TNFα) or glutamate, or deprivation of glucose ( 17 20 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, we established that Th17-polarized cells induce both OL process damage and OL cell death in mouse and human systems. While we identified the contribution of CD29-triggered glutamate secretion by Th17-polarized cells to OL process injury and myelination impairment, glutamate did not induce death of human OLs in primary culture ( 17 ). Human OLs are highly resistant to induction of programmed cell death upon exposure to stressors such as high doses of tumor necrosis factor alpha (TNFα) or glutamate, or deprivation of glucose ( 17 20 ).…”
Section: Introductionmentioning
confidence: 95%
“…We have recently reported that Th17 cells can form prolonged contact with OLs in vivo in EAE ( 17 ). In addition, we established that Th17-polarized cells induce both OL process damage and OL cell death in mouse and human systems.…”
Section: Introductionmentioning
confidence: 99%
“…Visweswaran et al observed a sustained decrease in the frequency of the Th17 subset at both 24 and 36 months, but with no change in absolute Th17 cell numbers [ 36 ]. Of note, Th17 is thought to directly participate in MS-associated neuroinflammation and damage oligodendrocytes [ 100 ]. Numerous studies report that CD4+ T cell populations do not return to baseline 2 years post-aHSCT, with altered CD4+ /CD8+ T cell ratios, therefore, persisting in the long term [ 47 , 62 , 96 , 97 , 101 ].…”
Section: Immune Reconstitution Following Ahsctmentioning
confidence: 99%
“…These measurements are dependent on the total time an object is being tracked, the time interval between images and the accuracy of the tracking analysis. Many studies have used velocity and angle to quantify T cell migration patterns 1,8,9,19,69‐71 . These measurements were important to elucidate the behavior patterns observed in the initial T cell priming and effector stages (Figure 1A).…”
Section: Approaches For Quantifying Immune Cell Behaviormentioning
confidence: 99%
“…Many studies have used velocity and angle to quantify T cell migration patterns. 1,8,9,19,[69][70][71] These measurements were important to elucidate the behavior patterns observed in the initial T cell priming and effector stages (Figure 1A). But to extract additional behavior patterns that are more subtle may require the integration of different measures.…”
Section: Approache S For Quantif Ying Immune Cell B Ehaviormentioning
confidence: 99%